New Co(II), Cu(II) and Ni(II) complexes with 1,2-bis(o-aminophenoxy)ethane - Tokmak, N.; Sekerci, M.; Temel, H. (Chem Soc Pakistan, 2006)
1,2-Bis(o-aminophenoxy)ethane was prepared in a one stage process. In this reaction, Pd/C was used as catalyst. 1,2-Bis(o-aminophenoxy)ethane was synthesized from 1,2-bis(o-nitrophenoxy)ethane. Diamine complexes [CoLCl(2)2H(2)O], [CuLCl2]0.5H(2)O and [NiL2(C2H5O)(2)] have been synthesized and characterized by elemental analyses, Lambda(M), IR, UV-VIS, H-1 NMR and magnetic measurements.
Keywords: Zn(Ii) Complexes; Schiff-Base; Transition; Manganese(Iii); Copper(Ii); Zinc(Ii)